청소년의 무단결석 경험이 자아인식과 정서문제에 미치는 영향 - 한국아동·청소년패널 자료를 중심으로 - 전구훈(Gu-Hun Jeon) (한국콘텐츠학회 논문지, 21(6), 2021)
The purpose of this study was empirical verification of the effect of adolescents' truancy experience on the self-awareness and emotional problems. For this, using the data of 2016 in the Korean Children and Youth Panel Survey(KCYPS), we compared and analyzed using t-test and multiple regression analysis the self-awareness and emotional problems of adolescents who experienced truancy and adolescents who did not. As a result of the analysis, adolescents with truancy experience had relatively low self-awareness, and statistically significant but low scores in self-identity and career identity. However, there was a clear difference in emotional problems, and truancy adolescents scored high in attention, aggression, physical symptoms, and depression. This proved that adolescents with experience of truancy were more exposed to emotional problems, and it was necessary to develop a support system and program for this. 본 연구는 청소년의 무단결석 경험 유무가 자아인식과 정서문제에 어떠한 영향을 미치는 지에 대한 실증적인 검증을 목적으로 설계되었다. 이를 위해 한국아동·청소년 패널조사의 2016년 자료를 활용하여 무단결석을 경험한 청소년과 경험하지 않은 청소년의 자아인식과 정서문제를 차이검증과 다중 회귀분석을 사용하여 분석하였다. 분석결과 무단결석 경험이 있는 학생들은 자아인식이 상대적으로 낮았고, 자아정체감과 진로정체감에서 통계적으로 유의미하였지만 낮은 점수를 나타냈다. 그러나 정서적인 문제에서는 분명한 차이가 나타났는데 주의집중, 공격성, 신체증상, 우울에서 무단결석 학생이 높은 점수를 보였다. 이는 무단결석 경험이 있는 학생들이 정서문제에 더 노출되어 있는 것으로 증명되었으며, 이에 대한 지원시스템과 프로그램 개발이 필요함을 확인하였다.